Assessment of 7 Inflammatory Indexes as an Early Predictor of COVID-19 Severity - Çalışkan, Zeynep; Bozdağ, Emre; Sönmez, Süleyman; Dağıstanlı, Sevinç; Bulut, Nurgül; Dinçer, Yıldız (Cerrahpaşa Medical Journal, 2022)
Objective: Early identification of severe patients with coronavirus disease 2019 is important for reducing mortality rates. The current study was conducted to evaluate the predictive value of certain inflammatory indexes, including C-reactive protein to albumin ratio, fibrinogen to albumin ratio, procalcitonin to albumin ratio, procalcitonin to CRP ratio, neutrophil to lymphocyte ratio, monocyte to lymphocyte ratio, and platelet to lymphocyte ratio for the severity of coronavirus disease 2019. We aimed to assess whether these indexes could be efficient early indicators of severe disease. Methods: Five hundred forty-eight hospitalized coronavirus disease 2019 patients were divided into 2 groups according to their condition: nonsevere group (n = 435) and severe group (n = 113). Results: Severe coronavirus disease 2019 patients had higher C-reactive protein to albumin ratio, fibrinogen to albumin ratio, procalcitonin to albumin ratio, neutrophil to lymphocyte ratio, monocyte to lymphocyte ratio, and platelet to lymphocyte ratio compared with nonsevere patients (P < .05). Logistic regression analysis demonstrated that C-reactive protein to albumin ratio (OR, 1.359; 95% CI, 1.143-1.615) and D-dimer (OR, 1.054; 95% CI, 1.010-1.100) were the independent risk factors for severe coronavirus disease 2019. The area under the curve for C-reactive protein to albumin ratio, fibrinogen to albumin ratio, procalcitonin to albumin ratio, neutrophil to lymphocyte ratio, monocyte to lymphocyte ratio, and platelet to lymphocyte ratio was 0.763, 0.629, 0.681, 0.708, 0.605, and 0.644, respectively. Conclusion: C-reactive protein to albumin ratio was the best inflammatory predictor compared with other indexes for the early identification of severe coronavirus disease 2019 and it was demonstrated for the first time that procalcitonin to albumin ratio could be used to evaluate disease severity of coronavirus disease 2019 with relatively high sensitivity. Cite this article as: Çalışkan Z, Bozdağ E, Sönmez S, Dağıstanlı S, Bulut N, Dinçer Y. Assessment of 7 inflammatory indexes as an early predictor of COVID-19 severity. Cerrahpaşa Med J. 2022;46(2):156-163.